Pengaruh Jenjang Pendidikan dan Pemahaman Teknologi Informasi Terhadap Penyajian Laporan Keuangan Berdasarkan SAK ETAP (Studi Kasus Di Kampung Batik Laweyan) - Rina Puji Hastuti; Anita Wijayanti; Yuli Chomsatu (UNSIKA (Universitas Singaperbangsa Karawang), 2017)
This research aims to know influence of knowledge level and information technology comprehensive on conformity of financial statement presentation based on SAK ETAP. Sample of this research is 100 batik’s craftsmen in Kampung Batik Laweyan Surakarta. Technique to collect sample is random sampling. Instrument of this research is questionnaire. Data which have been collected is analyzed by assumption classic testing and regression testing. The result of this research is knowledge level influences positively on conformity of financial statement presentation based on SAK ETAP. While, information technology comprehensive doesn’t influence positively on conformity of financial statement presentation based on SAK ETAP.